2021
DOI: 10.3390/plants10040757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Superabsorbent Polymers and Variety on Yield, Quality and Physiological Parameters of the Sugar Beet (Beta vulgaris prov. Altissima Doell)

Abstract: In this study, we focus on the mitigation of the negative impact of drought using the application of superabsorbent polymers (SAPs) to seed. One way to monitor drought and quantify its impact on crops in field conditions is the nondestructive measurement of physiological processes of the crops using spectral indexes LAI and PRI during vegetation. Therefore, during 2018 and 2019, the increase in biomass and intensity of photosynthetic activity was monitored, and the effect of the SAPs application on the yield p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…This study found a significant influence of SAPs on the weight of leaves and roots of young plants, with significantly higher values of these traits in the SAP treatment condition. This is consistent with the findings of Pačuta et al (2021) that plants treated with SAPs could cope with drought stress better than those growing in the control condition. However, drought conditions during growth phases reduce the plant and leaf size due to decreased transpiration and photosynthesis (Devi et al 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This study found a significant influence of SAPs on the weight of leaves and roots of young plants, with significantly higher values of these traits in the SAP treatment condition. This is consistent with the findings of Pačuta et al (2021) that plants treated with SAPs could cope with drought stress better than those growing in the control condition. However, drought conditions during growth phases reduce the plant and leaf size due to decreased transpiration and photosynthesis (Devi et al 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Jarecki and Wietecha [ 22 ] observed a 0.5-t ha −1 higher yield of soybean from coated seeds in unfavorable conditions. In the experiments of Pačuta et al [ 23 ], the synthetic polymer Aquaholder ® Seed, the same as in our experiment, was used to treat sugar beet seeds and the positive effect of SAP on the leaf area index, root yield, and sugar yield was confirmed.…”
Section: Introductionmentioning
confidence: 55%
“…Total nitrogen content was determined in spring as 8.10 mg kg −1 for 2021 and 11.70 mg kg −1 for 2022. The ammonia form of nitrogen was determined calorimetrically using Nessler's reagent [41] and the nitrate form calorimetrically using phenol 2.4-disulfonic acid, as in Pačuta et al [42]. The Mehlich III test was used to determine the phosphorus and potassium content in the soil [43].…”
Section: Experimental Setup and Designmentioning
confidence: 99%